Pocket book of English grammar for engineers and scientists - Finkelstein, Leo Jr. (Boston, 2007)
This book is designed to provide you with the information you need to quickly and effectively understand and use the major concepts of English grammar in your technical reports and presentations.
Keywords: English Language-Grammar